2019
DOI: 10.1007/s00468-019-01828-3
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific responses of growth and biomass distribution to trellis availability in three temperate lianas

Abstract: Key message In some lianas the use of trellis modifies within-plant biomass allocation and stimulates growth, however in other species trellis use may negatively affect growth indicating a cost associated with climbing. Abstract In order to improve access to light, lianas use other plants as climbing trellises. Whereas in shaded lianas climbing a trellis may enhance biomass gain by increasing leaf-level irradiance, we suspected that trellis use may also stimulate growth by triggering modifications in whole-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Though little is known about the switch between the self-supporting and climbing phases, a fast pace of vertical expansion or bending is necessary in the search for support [64,65]. Having a higher SSL is an easy way to gain such support [66], although it may adversely affect its self-support and stem stability [67]; however, once support is gained, the longer stem or bigger SSL, as compared with trees, pays off.…”
Section: Direct Traits Comparison Between Lianas and Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Though little is known about the switch between the self-supporting and climbing phases, a fast pace of vertical expansion or bending is necessary in the search for support [64,65]. Having a higher SSL is an easy way to gain such support [66], although it may adversely affect its self-support and stem stability [67]; however, once support is gained, the longer stem or bigger SSL, as compared with trees, pays off.…”
Section: Direct Traits Comparison Between Lianas and Treesmentioning
confidence: 99%
“…Higher per unit of dry mass used in organs (leaves, stems, and roots) indicates strategies of resource optimization. Both higher SLA and LAR in species of the liana-dominated cluster suggested they optimized their already limited dry leaf mass to capture light [67]. SLA and LAR are classic traits which are thought to be of paramount importance for plant performance [49].…”
Section: Pattern Of Dry Matter Content and Per Dry Mass Unit Investme...mentioning
confidence: 99%
“…The fruits of E. lobata can be developed at different heights because of the climbing strategy. In some climbing plants, the use of external support modifies biomass allocation and stimulates growth, whereas in other species, it may negatively affect growth, indicating a cost associated with climbing [1,61]. Moreover, the non-climbing plants that provide mechanical support for the climbing plants are also competitors for light, water, and nutrients [1,62].…”
Section: Discussionmentioning
confidence: 99%
“…For a plant species that is incapable of growing upright on its own, the optimal circumstance is to climb a tree or other support, which allows it to maximise its photosynthetic capacity. Ground‐based vegetative spread permits an established liana to expand its range, albeit incrementally, while searching for trees to support its stems (Wyka et al, 2019). Research has shown that many species of creeping lianas can produce dense networks of branching stems, both above and below ground (Buru et al, 2016; Leicht‐Young et al, 2011; Putz, 1984; Sakai et al, 2002; Schnitzer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%